Prevalence, Characteristics, and Distribution of Oral and Maxillofacial Lesions in the Libyan Population of Benghazi- A Ten-Year Retrospective Study - haroun, Ghada H; Aguori, Eman; El Murtady, Ali (AlQalam Journal of Medical and Applied Sciences, 2025)
The oral and maxillofacial region can be affected by a variety of medical conditions, ranging from mild inflammatory conditions to true benign and malignant neoplasms. This study aimed to provide a systematic analysis of oral and maxillofacial lesions in a Libyan population over a decade, and to compare the results with the reports from other countries. The patient’s records were retrieved from the Department of Oral Medicine, Oral Pathology, Diagnosis, and Radiology's archive and reviewed during the period from 2010 to 2019. Patient demographic information (age and sex) and lesion location were recorded and analysed. During the period of study, a total of 593 biopsies were confirmed as oral and maxillofacial lesions, showing a male-to-female ratio of 0.8:1, and a mean age of 38.66±18.137 years. The non-neoplastic lesions accounted for much of the sample (79%), with the reactive and inflammatory lesions being the most observed. Among the neoplastic lesions, benign non-odontogenic tumours constituted 39.7% of the total, primarily in the form of squamous cell papilloma. Odontogenic tumours were less common (17.46%), with the ameloblastoma being the most frequently observed type. Malignant tumours constituted about 8.9% of the total biopsies, with squamous cell carcinoma being the most common, accounting for 5.4% of all the lesions. In conclusion, most of the oral and maxillofacial lesions during the study period were non-neoplastic in nature, mainly affecting middle-aged women, with fibroepithelial polyp and radicular cyst being the most frequent diagnoses.